Development of a micro crystallisation system for the production of sub-micron particulates with narrow-size-distribution - Alghaffari, Nabeel Kadhim Abbood (2015)
Recent advancements in applied, medical materials engineering sciences and micro/nano technology have stimulated increasing demand for novel, high quality and precisely-shaped particles. As most of the materials that are used by these scientific fields are in crystalline forms, it is evident that crystallization, in particular micro-scale crystallisation is a very useful tool to satisfy this demand. This research charts the investigation and optimisation of micro-scale continuous crystallisation of a fine and commonly used compound, i.e. paracetamol, with attempts to overcome the limitations of such process, for instance to produce particles with narrow particle size distribution and maintain a smooth and continuous operation without microchannel blockage. In this thesis, efforts have been directed to design and test a micro scale continuous crystalliser using two different crystallisation techniques; namely: cooling down of saturated solution and adding antisolvent agent. The former technique was not so successful due to the difficult thermal control of such microfluidic system with available resources, as well as due to the inherent nature of such crystallisation mode, which required long induction time to start crystallisation. The latter technique, on the other hand, was successful due to the short induction time required to drive crystallisation and it does not require any thermal management, as it is performed at ambient temperature. Using the antisolvent technique require very short mixing time to mix the mother liquor with an antisolvent agent to produce supersaturated solution. This was achieved by proposing a novel microfluidic design consisting of baffled microchannel devices operated by superimposing a fully reverse oscillatory flow to facilitate fast non-axial mixing regardless of the very low axial flow rate that is typical to microfluidic devises. Computational fluid dynamics simulations in addition to microfluidic flow visualisation experiments were carried out to examine the non-axial mixing performance for the proposeddesign. Subsequently, the proposed design was tested as a con- tinuous crystalliser and showed very good performances by producing sub-micrometre particles with a very narrow particle size distribution. Finally, the performance of the micro scale continuous crystalliser was optimised to produce particle with minimum particle size using custom design of experiment technique. Results of this optimisation process were successful and produced paracetamol particles having average Z-Ave = 99.89 nm with standard deviation equivalent to 7.315 nm. Finally, this thesis shows a successful demonstration of a simple yet versatile microcrystallisation system capable of producing particles of consistent size by utilising fully reverse oscillatory flow into baffled microchannel.